STEROIDS FROM Chisocheton tomentosus - A. Najmuldeen, Ibrahim; A. Hadi, A. Hamid; Awang, Khalijah; Fadaei Nasab, Mehran; Ketuly, Kamal Aziz; Mukhtar, Mat Ropi; Morita, Hiroshi (Malaysian Journal of Science, 2011)
Four steroids have been isolated from dichloromethane extract of Chisocheton tomentosus (Meliaceace), they were; 7Î±-hydroxy-Î²-sitosterol 1, stigmasta-4,6-diene-3-one 2, stigmasterol 3 and sitosterol 4. 7Î±- Hydroxy-Î²-sitosterol 1 was isolated as a colourless crystal and this compound was a new compound in crystal structure. The isolation and purification of the compounds were achieved by using column and PTL chromatographic techniques. The compounds were identified by spectroscopic techniques such as UV, IR, MS, 1D, and 2D NMR. In addition; 7 Î± -hydroxy -Î²-sitosterol was also identified by X-Ray diffraction technique. (Key word: Meliaceace, Chisocheton tomentosus, steroids )